Model of Creative Economy Supply Chain Resilience to Improve SME Sales - Muzakar Isa; Liana Mangifera (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
Supply chain resilience, which consists of robustness, flexibility, and agility, are critical to maintaining business productivity and sustainability. The objective of this research is to scrutinize the robustness and adaptability in relation to agility, in addition to examining the impact of flexibility and agility on the sales of SMEs. Data was amassed through structured interviews with 314 proprietors of food and beverage businesses in Surakarta. The analytical method utilized was one of the structural equation modeling techniques, specifically, Partial Least Square (SEM-PLS). The analytical outcomes suggest that to bolster the sustainability of food and beverage enterprises, SMEs must exhibit agility and adaptability during periods of uncertainty in the business environment, supported by a robust supply chain. Moreover, agility partially functions as a mediator in the robustness and flexibility of SMEs in relation to sales. The implications of this research underscore the necessity for support from all stakeholders in the food and beverage supply chain activities to ensure SMEs are resilient, agile, and adaptable in confronting dynamic environmental challenges.